Efusi Pleura dan Asites pada Anak dengan Demam Berdarah Dengue dan Penatalaksanaannya: Laporan Kasus - Asterisa Retno Putri; Runi Arumndari; Claudia Natasha Liman; Anak Agung Made Sucipta (Cermin Dunia Kedokteran, 2025)
Background: Dengue haemorrhagic fever (DHF) is caused by dengue virus type 1-4; it is still endemic in Indonesia. Case: A 1 year and 11 months--old baby-girl with fever, lethargic, nausea and vomiting, and thrombocytopenia. She was diagnosed with dengue hemorrhagic fever. Pleural effusion and ascites were diagnosed after fluid resuscitation. Clinical improvement was observed after furosemide therapy and could be discharged after seven days of treatment. Conclusion: Diuretic administration can be considered in case of dengue haemorrhagic fever with severe plasma leakage. Further research is needed.